The Pro12Ala Polymorphism of the Peroxisome Proliferator-Activated Receptor Gamma Gene Modifies the Association of Physical Activity and Body Mass Changes in Polish Women. (13th October 2014) - Zarebska, Aleksandra; Jastrzebski, Zbigniew; Cieszczyk, Pawel; Leonska-Duniec, Agata; Kotarska, Katarzyna; Kaczmarczyk, Mariusz; Sawczuk, Marek; Maciejewska-Karlowska, Agnieszka
Abstract : Peroxisome proliferator-activated receptorγ is a key regulator of adipogenesis, responsible for fatty acid storage and maintaining energy balance in the human body. Studies on the functional importance of the PPARG Pro12Ala polymorphic variants indicated that the observed alleles may influence body mass measurements; however, obtained results were inconsistent. We have decided to check if body mass changes observed in physically active participants will be modulated by the PPARG Pro12Ala genotype. The genotype distribution of the PPARG Pro12Ala allele was examined in a group of 201 Polish women measured for selected body mass variables before and after the completion of a 12-week training program. The results of our experiment suggest that PPARG genotype can modulate training-induced body mass measurements changes: after completion of the training program, Pro12/Pro12 homozygotes were characterised by a greater decrease of body fat mass measurements in comparison with 12Ala allele carriers. These results indicate that the PPARG 12Ala variant may impair the training-induced positive effects on body mass measurements; however, the detailed mechanism of such interaction remained unclear and observed correlation between PPARG genotype and body mass differential effects should be interpreted with caution.